Whole exome sequencing identifies a pathogenic mutation in WFS1 in two large Chinese families with autosomal dominant all-frequency hearing loss and prenatal counseling. (March 2018) - Cheng, Hongbo; Zhang, Qin; Wang, Wenbin; Meng, Qingxia; Wang, Fuxin; Liu, Minjuan; Mao, Jun; Shi, Yichao; Wang, Wei; Li, Hong
Abstract: Objectives: To identify the pathogenic mutation and provide prenatal counseling and diagnosis in two large Chinese families with autosomal dominant all-frequency hearing loss. Methods: Whole exome sequencing technology was used to identify the pathogenic mutation of the two families. In addition, 298 patients with sporadic hearing loss and 400 normal controls were studied to verify the mutation/polymorphism nature of the identified variant. Prenatal diagnosis was carried out. Results: A rare missense mutation c.2389G > A (p.D572N) in the Wolframin syndrome 1 ( WFS1 ) gene was identified. It was reported in only one previous Chinese study, and never in other populations/ethnicities. The mutation was also found in one patient with sporadic hearing loss (1/298, 0.3%). A healthy baby was born after prenatal diagnosis. Conclusion: Our findings strongly suggest that the c.2389G > A mutation in WFS1 is associated with all-frequency hearing loss, rather than low- or high-frequency loss. So far, the mutation is only reported in Chinese. Prenatal diagnosis and prenatal counseling is available for these two Chinese families.